Acute dual antiplatelet therapy for minor ischaemic stroke or transient ischaemic attack. (28th February 2019) - Wang, Yongjun; Johnston, S Claiborne; Bath, Philip M; Grotta, James C; Pan, Yuesong; Amarenco, Pierre; Wang, Yilong; Simon, Tabassome; Kim, Jong Sung; Jeng, Jiann-Shing; Liu, Liping; Lin, Yi; et al.
Abstract : Yongjun Wang and colleagues discuss recent evidence for using dual antiplatelet therapy to reduce recurrence of stroke or transient ischaemic attack